Predicting Intention to Use Tumbler in Music Festival Using Extended Theory of Planned Behavior - Ocky Fadilla, Ferdy; Aikar Raida, Handaru; Ul Haq, Dhia; Agustini Muwarni, Ina (Journal of Research in Marketing (ISSN: 2292-9355), 2021)
Objective: Plastic waste in music festivals has been a concern for these few past years. In a way to tackle it, individuals have to possess green intentions. It is important to explore what determines individuals to possess green intention (intention to bring tumbler is considered a green intention in this research). Methods: Sample comprised of 260 Indonesian music festival-goers who took a survey online questionnaire. This study predicts green intention using the extended Theory of Planned Behavior model. Further data was analyzed using the PLS-SEM method with SmartPLS software. Result: The result showed that altruism is the strongest predictor and the most significant motivator, directly and indirectly, that influences goers’ intention to bring along tumblers to such events. Subjective norms and perceived behavioral control also showed a positive and significant result of green intention. Conclusion: Altruism played an important role in predicting individuals’ green intentions. Individuals tend to act green when their value is not self-centered or care for others.